2009
DOI: 10.1001/archsurg.2009.88
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Portal Venous Gas

Abstract: The finding of HPVG alone cannot be an indication for emergency exploration, and we have developed an evidence-based algorithm to guide the clinician in management of patients with HPVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(104 citation statements)
references
References 61 publications
1
101
1
1
Order By: Relevance
“…This latter result is likely a random finding and clinically insignificant, since PI and PMVG represent progressive steps in a single pathophysiological process. Gas progressively ascends from the bowel wall to the liver, extending through the arcade veins, the segmental veins, the superior mesenteric vein, and finally into the extra- and intrahepatic portal veins [1, 7, 19, 30]. Nevertheless, although significantly correlated with ischemia in our study, PMVG may result from various other conditions, as reported by Hussain et al [7], namely the increase of luminal pressure in case of obstructive and non-obstructive bowel dilatation as well as bacterial contamination of the portomesenteric venous system from the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…This latter result is likely a random finding and clinically insignificant, since PI and PMVG represent progressive steps in a single pathophysiological process. Gas progressively ascends from the bowel wall to the liver, extending through the arcade veins, the segmental veins, the superior mesenteric vein, and finally into the extra- and intrahepatic portal veins [1, 7, 19, 30]. Nevertheless, although significantly correlated with ischemia in our study, PMVG may result from various other conditions, as reported by Hussain et al [7], namely the increase of luminal pressure in case of obstructive and non-obstructive bowel dilatation as well as bacterial contamination of the portomesenteric venous system from the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…HPVG was recognized to be fatal in the 1980s, yet recent increases in cases have demonstrated that non-symptomatic HPVG is not necessarily fatal [13]. In the present case, there were no acute abdominal symptoms on physical examination, and a blood test showed pH 7.445, base excess 1.9 mmol/L, and lactate dehydrogenase 224 IU/l.…”
Section: Discussionmentioning
confidence: 53%
“…The mortality rate for HPVG with necrotizing colitis is approximately 75 % [11, 12], whereas the mortality rate for HPVG without necrotizing colitis is not as high, highlighting the importance of distinguishing whether cases of HPVG may be fatal or nonfatal particularly by ruling out necrotizing colitis [13]. In terms of HPVG as a PEG-related complication, only cases of HPVG occurring immediately following PEG insertion have been reported to date [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the available case reports of HPVG in blunt abdominal trauma indicate that the mortality is low and that this sign is not per se an indication for surgery. 10 Our patient showed no PI and was indeed operated for haemodynamic instability. The complete clearance of his HPVG within a week strengthens the view that it was a benign occurrence.…”
Section: Discussionmentioning
confidence: 60%